2015
DOI: 10.2134/jeq2014.10.0457
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus Mobilization from Manure-Amended and Unamended Alkaline Soils to Overlying Water during Simulated Flooding

Abstract: Anaerobic soil conditions resulting from flooding often enhance release of phosphorus (P) to overlying water. Enhanced P release is well documented for flooded acidic soils; however, there is little information for flooded alkaline soils. We examined the effect of flooding and anaerobic conditions on P mobilization using 12 alkaline soils from Manitoba that were either unamended or amended with solid cattle manure. Pore water and floodwater were analyzed over 8 wk of simulated flooding for dissolved reactive P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
98
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(127 citation statements)
references
References 47 publications
26
98
3
Order By: Relevance
“…DRP decreased 88.3% in VS and 85.0% in WS. The result was consistent with those of Amarawansha et.al [18] but different from those of Tian [36]. Tian et al found that DRP in floodwater decreased with time of flooding in amended acid soils.…”
Section: Standing Floodwater P Following Long-term Flooding Drainingsupporting
confidence: 88%
See 4 more Smart Citations
“…DRP decreased 88.3% in VS and 85.0% in WS. The result was consistent with those of Amarawansha et.al [18] but different from those of Tian [36]. Tian et al found that DRP in floodwater decreased with time of flooding in amended acid soils.…”
Section: Standing Floodwater P Following Long-term Flooding Drainingsupporting
confidence: 88%
“…Furthermore, Olsen P in VS was 106.9-274.2 mg/kg at 0-35 cm. The content of Olsen P in surface soil was 79.87-210.32 mg/kg, which was higher than that in the research of Amarawansha et al [18]. This will lead to increased soil P leaching into flood water and pore water and increased the risk of eutrophication of rivers and lakes from agricultural non-point source pollution.…”
Section: General Soil Propertiescontrasting
confidence: 54%
See 3 more Smart Citations